Improved seizure resistance of ultra-high-strength steel ironed cups with a lubricant containing SiO2 nanoparticles - Tan, C.J.; Aslian, A.; Abe, Y.; Mori, K. (Springer Verlag (Germany), 2016)
Good boundary lubrication is necessary during cold stamping of high-strength steel sheets to prevent die wear and seizure of the parts owing to the high contact pressure. This study is aimed to improve the seizure resistance in a 1-step combined process of deep drawing and ironing of ultra-high-strength steel cylindrical cups using a commercial lubricant containing SiO2 nanoparticles with an uncoated die. In this study, the extreme pressure performance of the lubricant containing 0.0, 0.5, 1.0, 1.5, 2.0 and 2.5 wt% of SiO2 was first evaluated using a deep drawing process under increased blank holding forces. The optimum concentration of SiO2 was determined, i.e. 2 wt%, based on successful drawing of cups having smooth surfaces under the highest holding force. Then, the ironing limits of the cups for the lubricants containing 0 and 2 wt% of SiO2 respectively were investigated with the 1-step combined process under increased ironing ratios. The experimental results showed that seizure was observed for the lubricant containing no nanoparticles at an ironing ratio of −16.7 %. However, no seizures were observed for ironing ratios up to 4.2 % using the lubricant containing 2 wt% of SiO2. The resistance to seizure of the cup was significantly increased, leading to the formation of cylindrical cups having smooth surfaces and uniform side wall thickness.